Analisis Faktor-Faktor Yang Mempengaruhi Organizational Citizenship Behavior Dan Dampaknya Terhadap Kinerja Guru Di Pesantren Darunnajah - Puspadina, Mafida; Yusuf, Furtasan Ali; Nuryanto, Uli Wildan (Jesya (Jurnal Ekonomi dan Ekonomi Syariah), 2024)
This study aims to determine the effect of work motivation and servant leadership on organizational citizenship behavior and their impact on teacher performance at Darunnajah Islamic Boarding School. Given the increasing demands of the community for improving the quality of Islamic boarding schools and the hope that they will have high competitiveness in the current global environment. The research used a quantitative approach with survey methods and data analysis methods using SEM PLS on 150 teachers at the Darunnajah Islamic Boarding School spread over twenty different Islamic boarding school locations. The results showed that all indicator items had good validity and reliability with factor loading values above 0.70 and reliability values in the form of CR and Alpha Cronbach’s above 0.70. The results of the inner model analysis show that the model has a good predictive relevance value and the path coefficient results show a positive effect of work motivation and servant leadership on OCB and teacher performance. Meanwhile, the hypothesis results show that of the 7 hypotheses tested, all hypotheses were accepted. Which means that work motivation has a significant effect on OCB and teacher performance. The same is true with servant leadership which has a significant effect on OCB and teacher performance, so is the case with OCB on teacher performance. The results of the mediation test showed that OCB was able to be a good mediating variable for work motivation on teacher performance and servant leadership on teacher performance at Darunnajah Islamic Boarding School